Prognostic Value of Pretreatment Controlling Nutritional Status Score for Patients With Pancreatic Cancer: A Meta-Analysis - Ma, Xiaofeng; Zou, Weihua; Sun, Yu (Frontiers in Oncology, 2022)
Background Previous studies have explored the prognostic value of the pretreatment Controlling Nutritional Status (CONUT) score of patients with pancreatic cancer. However, the results of those studies were inconsistent. We used meta-analysis to investigate the impact of the CONUT score on the prognosis for patients with pancreatic cancer. Methods We thoroughly searched the PubMed, Web of Science, Embase, and Cochrane Library databases for relevant articles from inception to November 19, 2021. Combined hazard ratios (HRs) and 95% confidence intervals (95% CIs) were used to estimate the prognostic value of the CONUT score with respect to survival duration. The pooled odds ratios (ORs) and 95% CIs were used to estimate the correlation between the CONUT score and clinical characteristics. Results The database search found seven studies with 2,294 patients for inclusion in this meta-analysis. A high CONUT score was significantly associated with poor overall survival (OS) (HR = 1.56, 95% CI = 1.13–2.16, p = 0.007), but not with recurrence-free survival (RFS) (HR = 1.47, 95% CI = 0.97–2.23, p = 0.072) of patients with pancreatic cancer. Moreover, there was a significant association between an elevated CONUT score and male patients (OR = 1.34, 95% CI = 1.03–1.75, p = 0.029). However, there was no significant association between the CONUT score and the clinical stage (OR = 1.11, 95% CI = 0.46–2.71, p = 0.576), lymph node metastasis (OR = 0.73, 95% CI = 0.39–1.36, p = 0.323), lymphatic vessel invasion (OR = 0.84, 95% CI = 0.55–1.28, p = 0.411), invasion of the portal vein system (OR = 1.04, 95% CI = 0.51–2.13, p = 0.915), and nerve plexus invasion (OR = 1.22, 95% CI = 0.83–1.80, p = 0.318) in patients with pancreatic cancer. Conclusions The results of our meta-analysis indicate that a high CONUT score predicts a poor OS in patients with pancreatic cancer. The CONUT score may be an effective prognostic factor in pancreatic cancer in clinical practice.